A Note on Moral Licensing and Foot-In-The-Door Effect - Alistair Ulph; Luca Panzone; Denis Hilton (Center for Economic Studies and ifo Institute (CESifo), 2019)
Literature in economics and psychology on moral behaviour explores the contexts in which people act in ways that are consistent or inconsistent with their past actions. Such inconsistencies appear to violate economists' assumption of rational consumer behaviour. In this note we show that a simple model of rational (utility-maximising) consumer behaviour, in both static and dynamic forms, can explain both consistent and inconsistent behaviour.
Keywords: D11; H41; M31; Q56; Q58; 330; behavioural consistency; moral self-regulation; moral licensing; consumer behavior; sustainable consumption